Reconstructing Justice in Land Acquisition for Public Interest in Indonesia from the Perspectives of Legal Pluralism Werner Menski - Hayati, Muslimah; Noor Anugrah, Fajrian; Setiawan, Dri; Budiono, Arief; Ali Polatjon Ogli, Turdialiev Mukhammad (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This article examines the recurring gap between the normative principle of justice in land acquisition regulations for public interest development and the reality of its implementation in Indonesia. This study highlights recurring conflicts, weak community participation, and socio-cultural tensions that arise in state-driven development projects. Purposes of the Research: This study aims to analyze issues of justice in land acquisition for public purposes and reconstruct a more balanced model of justice using Werner Menski's legal pluralism, which integrates state law, social norms, and moral-ethical values. Methods of the Research: This study employs normative legal research, adopting a legislative, conceptual, and philosophical approach. Analysis was conducted on the regulatory framework, land acquisition principles, and the application of Menski's triangular legal pluralism model to assess the gap between norms and field practices. Results of the Research: Findings reveal that the dominance of state-centered legal positivism in land acquisition often neglects socio-cultural values and moral dimensions of justice, resulting in social conflict, marginalization, and inequality. As its principal novelty, this study reconstructs the concept of justice in land acquisition through a pluralistic, participatory, and contextual model. This model integrates state law, living law, and ethical considerations, promotes meaningful community participation in decision-making processes, and adapts legal implementation to local socio-cultural realities. In doing so, it seeks to balance legal certainty, social legitimacy, and substantive justice in the governance of land acquisition.